Analisis Konsentrasi Karbon Monoksida (CO) dan Oksida Sulfur (SOx) di Udara Ruangan Akibat Pembakaran Briket Ampas Sagu - Hafidawati, Hafidawati; Yenie, Elvi; Naufal, Hafiz Aulia; Manan, Abdul (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2024)
Sungai Tohor area, Meranti Islands, Riau, is a producer of sago in Indonesia and has great potential as a producer of sago flour. Sago flour production also produces waste in the form of sago dregs. Sago utilisation in Meranti Regency is still limited, sago stems (tual) are processed in factories (sago refineries) to produce sago flour with a production volume of 450,000 tonnes/year. This sago processing also produces side waste in the form of sago pulp as much as 75-83%. This provides potential in the utilisation of sago pulp as an environmentally friendly alternative energy source. This research aims to develop biopellets from sago pulp as a biomass fuel that can replace fossil fuels. The analysis results show that sago pulp biopellets have a moisture content of 8.22%, ash content of 30.51%, volatile matter of 22.01%, and calorific value of 4,599 cal/gr, which fulfils the SNI 01-6235-2000 standard. The CO and SOx gas emission measurements from the combustion of biopellets were below the threshold set in the Regulation of the Indonesian Minister of Health No. 1077 Year 2011 and SNI 7626-2013. The thermal efficiency of combustion reached 28.15%, indicating that sago pulp biopellets have great potential as an efficient and environmentally friendly biomass fuel, supporting sustainable energy transition in Indonesia.